Redistribution of ground subtracks for aircraft noise calculations - Schwab Olivier (Noise Mapping, 2020)
For aircraft noise calculations, lateral flight dispersion is commonly represented by means of subtracks – a backbone track and side-tracks to each side of the backbone track – where each subtrack is assigned a movement percentage. Aircraft noise calculations impose quality demands on these subtracks, while the latter are often created based on limited information.